Extensão universitária e Pibex: um estudo sobre os projetos de extensão e a percepção dos discentes bolsistas da UFT - Ferreira Júnior, Geraldo José (Universidade Federal do Tocantins, 2019)
This dissertation seeks to analyze and understand the extent to which the extension policy practiced by the Federal University of Tocantins (UFT), having as a cut-off for the research the Institutional Extension Grant Program (PIBEX), has fostered the university's interaction with other sectors of the society, through the analysis of the extension projects approved by said program, as well as to understand how the perception of these extensionist practices by the scholarship students who are involved in this process. To do so, initially, a survey was made of the institutional documents related to UFT's extension policy in order to confront them with the main guidelines and norms of university extension in Brazil. It should be emphasized that the national policy of extension and, consequently, that of the institution under study, is in permanent process of discussion, resignification and implementation due to its unfinished character and still under construction. With a qualitative and quantitative approach, the exploratory and descriptive research also included bibliographical and documentary research and the application of questionnaires to fellow scholars participating in the Academic PIBEX in 2016 in order to understand the perception of these subjects about the extensionist policy of UFT. In this sense, to support the study, we used as theoretical reference: (I) authors already consecrated in the studies about the university extension in the country, such as Fagundes (1986), Gurgel (1986), Botomé (1996), Souza 2000), Melo Neto (2001), Nogueira (2005) and Cunha (2007); (II) the debates and documents proposed by the Forum of Pro-Rectors of Extension of the Public Institutions of Higher Education in Brazil (FORPROEX); and, finally, (III) the extension regulations developed within the UFT. With regard to the extension policies of the university under study, it was verified that the norms, guidelines and conceptions about extension are in line with the main national guidelines developed by FORPROEX; as far as the perception of the students is concerned, it was found through the questionnaires that their perceptions are largely matured and understood, but with regard to the aspects related to the dissemination of university extension in UFT, it was observed the need for greater publicity among the students in order to further strengthen the extensionist practices in UFT.